PENGARUH CORPORATE GOVERNANCE, LEVERAGE DAN INTENSITAS PERSEDIAAN TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Fatma Mundriasari; Zirman Zirman; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to analyze the influence of corporate governance, leverage, inventory intensity to tax avoidance. Dependent variable in this research is tax avoidance as measured by cash effective tax rate. The independent variables used in this study are corporate governance proxied by board of commissioners, independent commissioners, audit committees, compensation of commissioners and board of directors, institutional investors. Then other independent variables in this research are leverage and inventory intensity.The sample of this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2013-2014. The sample was collected by purposive sampling method and produced 40 companies as sample. Data analysis using classic assumption test, hypothesis determination with multiple linear regression test, and determination test of R2. The result of this research indicates that variable of board of commissioner, independent commissioner, compensation of board of commissioner and board of directors, leverage have influence to tax avoidance. While the audit committee variables, institutional investors, and inventory intensity show the result that the variable has no effect on tax avoidance.Keywords : Tax Avoidance, Board of Commissioners, Independent Commissioner, Audit Committee, Compensation of Commissioners and Board of Directors, Institutional Investors, Leverage, Inventory Intensity.